2014
DOI: 10.1128/aac.02591-12
|View full text |Cite
|
Sign up to set email alerts
|

Potential Efficacy of Citicoline as Adjunct Therapy in Treatment of Cerebral Malaria

Abstract: bCerebral malaria (CM) is characterized by a dysregulated immune response that results in endothelial membrane destabilization and increased microparticle (MP) production. Citicoline (CTC) is a membrane stabilizer used for the treatment of neurological disorders. We evaluated the efficacy of CTC as adjunct therapy to aid recovery from experimental CM. We show that CTC reduces MP production in vitro; in combination with artesunate in vivo, confers partial protection against CM; and prolongs survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…In this study, Citicoline treatment led to diminished Annexin V/ PI fluorescence intensity, indicating the ability of Citicoline to lower apoptotic cell death in transmitochondrial AMD cells. This is consistent with a previous study in which the apoptosis inhibitory action of Citicoline was demonstrated using Annexin V/ FITC Flow cytometry analysis in a mouse model of cerebral malaria (CM); administration of Citicoline rescued cells in an experimental model of CM in vitro as well conferred partial protection against cell death and neurological syndrome in murine CM [17].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, Citicoline treatment led to diminished Annexin V/ PI fluorescence intensity, indicating the ability of Citicoline to lower apoptotic cell death in transmitochondrial AMD cells. This is consistent with a previous study in which the apoptosis inhibitory action of Citicoline was demonstrated using Annexin V/ FITC Flow cytometry analysis in a mouse model of cerebral malaria (CM); administration of Citicoline rescued cells in an experimental model of CM in vitro as well conferred partial protection against cell death and neurological syndrome in murine CM [17].…”
Section: Discussionsupporting
confidence: 92%
“…In vivo experiments showed that mice treated with pantethine 24 h post-infection with P. berghei did not display any signs of CM, which was attributed to two crucial events: diminished platelet reactivity, and downregulated EV production [ 83 ]. Another compound, citicoline, was found to reduce EV production in human brain ECs in vitro, and significantly enhance survival of mice with CM when used in combination with artesunate [ 85 ]. Citicoline is a widely available dietary supplement that occurs naturally in eukaryotic cell membranes and plays a role in membrane stability.…”
Section: The Pathogenesis Of Malaria: a Potential Role For Evsmentioning
confidence: 99%
“…Adjunct treatments that act through alternate mechanisms and address one or more of the pathogenic processes are urgently needed for a full rate recovery. Till date, a number of agents such as exogenous nitric oxide (NO) donor-dipropylenetriamine-NONOate (Zanini et al 2012), membrane stabilizer citicoline (El-Assaad et al 2014), mTOR inhibitor rapamycin (Gordon et al 2015) have been tested in ECM model as effective adjunct treatment. Atorvastatin, a lipid-lowering agent prevents cytoadhesion and endothelial damage under in vitro condition (Taoufiq et al 2011) and had shown protection in ECM model in combination with dihydroartemisinin (Dormoi et al 2013) and mefloquine (Souraud et al 2012).…”
Section: Discussionmentioning
confidence: 99%